2011
DOI: 10.2169/internalmedicine.50.5407
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Ambroxol against Paraquat-induced Pulmonary Fibrosis in Rats

Abstract: Objective To evaluate the possible therapeutic effect of ambroxol on pulmonary fibrosis induced by paraquat. Methods Adult male Sprague-Dawley rats (n =144, 200-250 g) were divided into four groups (Control, Ambroxol, Paraquat, and Paraquat+Ambroxol group) and sacrificed on day 1, 3, 5, 7, 14 and 28. Several significant oxidant stress markers (MDA, SOD and GSH-PX), MPO activity, cytokines (TNF-α, MCP-1, TGF-β1, MMP-2 and TIMP-1), total inflammatory cell count, hydroxyproline content, collagen I and III mRNA we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
2
13
0
1
Order By: Relevance
“…Ambroxol administration has been reported to suppress the lipopolysaccharide-induced production of TNF-α, IL-1β, interleukin-6 (IL-6), superoxide, hydrogen peroxide, and nitric oxide derived from rat macrophages in vitro 23 . In rats with paraquat-induced lung fibrosis, the protective effect of ambroxol was histologically prominent and presumably mediated by its free radical scavenging and antioxidant activity 8 . The results of our study of the effects of ambroxol treatment on quartz-induced lung inflammation in rats are consistent with these observations.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Ambroxol administration has been reported to suppress the lipopolysaccharide-induced production of TNF-α, IL-1β, interleukin-6 (IL-6), superoxide, hydrogen peroxide, and nitric oxide derived from rat macrophages in vitro 23 . In rats with paraquat-induced lung fibrosis, the protective effect of ambroxol was histologically prominent and presumably mediated by its free radical scavenging and antioxidant activity 8 . The results of our study of the effects of ambroxol treatment on quartz-induced lung inflammation in rats are consistent with these observations.…”
Section: Discussionmentioning
confidence: 97%
“…It has also been demonstrated that two intravenous injections of 20 mg/kg ambroxol hydrochloride with a 6-h interval stimulated synthesis and secretion of exogenous pulmonary surfactant in the lungs and exerted a protective effect in SD rats against pneumonia induced by Pseudomonas aeruginosa 7 . Paraquat-induced lung damage was reduced by a 28-day consecutive administration of ambroxol at a dose of 35 mg/kg 8 . However, there have been no studies that have explored potential effects of ambroxol on instilled particle-induced lung inflammation in F344 rats.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [21] showed that IL-6 plasma levels were not elevated at 6 and 12 hours in a PQ-intoxicated rat model (50 mg/kg), although a different study showed that IL-6 levels in lung tissues were higher 1 day after PQ injection in a rat model (18 mg/kg) [25]. Although some studies have suggested that TNF-α is involved in PQ-induced lung injury [26,27], the time sequence and peak of TNF-α have yet to be revealed in PQ intoxication. Therefore, it is necessary to investigate time sequence variation in IL-6 and TNF-α in PQ intoxication further.…”
Section: Discussionmentioning
confidence: 99%
“…L'ultime recours en cas de fibrose pulmonaire grave reste la greffe pulmonaire mais son succès est aléa-toire [2,12]. Certaines publications font état de travaux en cours sur d'autres molécules, comme des antioxydants tels que la N-acétylcystéine, la vitamine C, l'acide salicylique, la défé-roxamine ou encore l'ambroxol [15,[19][20][21].…”
Section: Discussionunclassified